TERAPI SPIRITUAL TERHADAP KECEMASAN DAN DEPRESI PADA PASIEN HEMODIALISIS : LITERATUR REVIEW - Erlangga Galih Zulva Nugroho; Heryanto Adi Nugroho; Abdurrahman Abdurrahman; Henni Kusuma (JOURNAL KEPERAWATAN, 2022)
In the end-stage renal disease of CKD, the patients should be hemodialysis to stabilize the state of the kidney function. Increased psychological problems such as anxiety and depression resulting from CKD complications and the consequences of hemodialysis programs performed on patients. It is important for nurses to provide psychological support to patients. The application of complementary therapies such as spiritual therapy is essential. The purpose of this study was to explore various forms of spiritual therapy in hemodialysis for anxiety and depression. This study used electronic database were identified from MEDLINE, CINAHL, Proquest, and GARUDA. The criteria of the paper in this study are : articles published at 2012 – 2020, full text, the article using English or Bahasa Indonesia, and the method of study using experimental study. We extracted 6 intervention studies and critical analyzes used PICO (Population, Intervention, Comparator, Outcome) method. After applying spiritual therapy, several studies resulted in average scores of anxiety and depression that decreased in the intervention group, including Self Paced Therapy, Prayer, Dhikr, Murotal Holy Quran and Spiritual Counseling. In addition, this therapy also has a positive impact on some aspects of the patient's life include the physical and social relationships. Based on the analysis of the results some studies on CKD patients with hemodialysis therapy for anxiety and depression experienced the results obtained that spiritual therapy like include self-paced, prayer and dhikr therapy, and spiritual counselling can decrease anxiety and depression.